The Relationship between Serum Levels of Hs-CRP and Coronary Lesion Severity - Razban, Mohammad Mehdi; Eslami, Masoud; Bagherzadeh, Ataollah (Medicine and Pharmacy Reports, 2016)
Background and aim. It is very important to know the risk factors of coronary artery disease and the role of inflammatory markers. One of these markers is hs-CRP that has been indicated to increase in patients with coronary artery atherosclerosis. The main objective of this study was to determine the relationship between serum levels of hs-CRP and coronary lesion severity. Methods. In the current study, we evaluated the role of hs-CRP in coronary artery disease and measured the relationship between serum hs-CRP levels and the severity of coronary lesions in 102 patients who referred to Imam Khomeini Hospital, Iran. The number of involved coronary arteries was measured. The severity of coronary lesions was evaluated by Gensini scoring method and the association between severity of coronary artery lesions and serum hs-CRP levels and other risk factors were examined. Results. No significant difference was found between the two groups in terms of gender. Severity of lesions had no significant difference according to Gensini score in women compared with men. Mean Gensini score was significant between the two groups (66.79±48.12 in hs-CRP positive group versus 21.09±26.25 in negative ones, p<0.05). In addition, diabetic patients were significantly more in hs-CRP positive group than negative hs-CRP group (P<0.05). In terms of smoking, there was a significant difference between the two groups. Percentage of patients with hypercholesterolemia was significantly higher in hs-CRP negative group. There was a significant difference in severity of lesions between smokers and non-smokers. Conclusion. No significant correlation was observed between serum levels of hs-CRP and severity and angiographic extent on coronary arteries in our study. Considering the potential risk of coronary inflammatory process as a new variable, it can help discover new cases of coronary lesions and follow-up and control of the selected cases.